La relación polémica entre la lógica de la filosofía y el dogma de la religión - Alshboul, Ayman M. Q. (Nómadas. Critical Journal of Social and Juridical Science, 2005)
The aim of this investigation is to analyze the polemic relationship between dogma (faith) and logic; in other words, studying the contradiction and/or the coincidence between religion and philosophy, also disputes and differences. Therefore religion like philosophy, they complement each other, and they are important and necessary for human beings; for their reciprocal relationship; accordingly, philosophy takes up logic and reasonable part of the human thought, while religion takes charge of the spiritual part of its life.